Uniting souls, discussing the nation, imposing oneself: gender, war and literature in correspondence sent by Teresa González de Fanning to José Enrique Rodó (1897-1901) - Santos, Elisângela da Silva [UNESP] (My University, 2024)
The text presents and discusses the letters from the Peruvian writer Teresa González de Fanning sent to the Uruguayan writer José Enrique Rodó. Our proposal is to reopen the archives to reveal an important facet of the author’s epistolary: the presence of women reflecting on the national and continental destiny. We conclude that the missives fulfill the role of bringing us closer to the theme of intellectual sociability of an author who accessed writing as a form of cultural and political expression.
Unir las almas, discutir la nación, imponerse: género, guerra y literatura en las correspondencias de Teresa Gonzáles de Fanning a José Enrique Rodó (1897-1901)
Unir as almas, discutir a nação, impor-se Gênero, guerra e literatura nas correspondências de Teresa González de Fanning a José Enrique Rodó (1897-1901)
Keywords: correspondence; Jose Enrique Rodó; literary sociability; Teresa González de Fanning